A TREM-1 Polymorphism A/T within the Exon 2 Is Associated with Pneumonia in Burn-Injured Patients. (12th February 2013) - Rivera-Chávez, Fernando A.; Huebinger, Ryan M.; Burris, Agnes; Liu, Ming-Mei; Minei, Joseph P.; Hunt, John L.; Arnoldo, Brett D.; Barber, Robert C.
Abstract : Background . The triggering receptor expressed in myeloid cells (TREM-1) is a key mediator in the activation of the local inflammatory response during lung infections. We aimed to evaluate the effect of a functionally relevant TREM-1 single nucleotide polymorphism within the exon 2 (A→T) on the development of pneumonia in burn patients. Objective . To determine whether a single nucleotide polymorphism (SNP) within the exon 2 (A→T) in the TREM-1 gene is associated with ventilator-associated pneumonia (VAP) in burn-injured patients. Methods . 540 patients with ≥10% total body surface area (TBSA) burn injuries or inhalation injury were prospectively enrolled. The influence of a polymorphism (A→T) in exon 2 of the TREM-1 gene was evaluated for association with increased risk of pneumonia by logistic regression analysis. Measurements and Main Results . 209 patients met criteria for VAP. Multivariate regression analysis showed that, after adjustment for potential confounders, we found that carriage of the TREM-1 T allele is associated with more than a 3-fold increased risk of VAP (OR 6.3, 95% CI 4–9). Conclusions . A TREM-1 single nucleotide polymorphism within the exon 2 (A→T) is associated with the development of pneumonia in burn patients.